The Influence of Picture Book Teaching on Children’s Aesthetic Ability: The Mediating Role of Teachers’ Aesthetic Imagination Cognition - Fang, Mengyan; Zhong, Shuxian (Advances in Social Sciences Research Journal, 2023)
Picture book teaching is one of the important ways to improve children’s aesthetic ability. Teachers’ aesthetic cognition of picture book teaching is the prerequisite for developing children’s aesthetic ability. This study aims to explore the current situation of teachers’ cognition of children’s aesthetic ability in picture book teaching and further examine the relationship between teachers’ cognition of children’s aesthetic ability in various dimensions. The results found that teachers’ overall cognition of children’s aesthetic ability in picture book teaching is at a moderately low level; teachers’ cognition of children’s aesthetic ability and its various dimensions are significantly positively correlated; teachers’ cognition of aesthetic creation can directly predict aesthetic ability cognition; teachers’ aesthetic imagination in picture book teaching has a mediating effect on aesthetic creation and aesthetic ability. Teachers should improve their aesthetic quality, fully explore the aesthetic resources of picture books, and promote the development of children’s aesthetic abilities.